Thermoelectric properties of Sn2+-substituted CuFeO2 delafossite-oxide - Ruttanapun, Chesta; Jindajitawat, Phumin; Thowladda, Warawoot; Neeyakorn, Worakarn; Thanachayanont, Chanchana; Charoenphakdee, Anek (My University, 2013)
This study aims to investigate the effect of the Sn2+-substituted into the CuFeO2 delafossite on thermoelectric properties in the Sn content of x = 0.03, 0.05. The CuFe1-xSnxO2 samples were synthesized by solid state reaction. The crystal structure was characterized by XRD, TGA, XPS and the thermoelectric properties were measured in the range of 300 to 960 K. The Seebeck coefficient display positive sign in all temperature range and the XPS show the stable Sn+2 state as confirming the Sn-doped CuFeO2 playing p-type conductor. The Sn2+-substituted supports the mixed valency Fe3+/Fe4+ state in transition octahedral oxide of FeO6 layer enhancing Seebeck coefficient. The high Seebeck are appeared in content of x=0.03 which are 280 to 340 μV/K in the range of 300 to 800 K. The experimental Seebeck corresponds to the prediction formula at high temperature. Totally, the maximum Power Factor is 2.30×10-4 W/mK2 occurring in the CuFe0.95Sn0.05O2 at 860 K which is higher than that value of the undoped-CuFeO2 in 4 times. These support that the Sn-substituted CuFeO2 delafossite enhancing thermoelectric properties. © (2013) Trans Tech Publications, Switzerland.
Keywords: CuFe1-xSnxO2; Mixed fe3+/fe4+valence; Sn2+ substituted; Thermoelectric properties